Development of a multiplex system for the identification of forensically relevant body fluids. (July 2020) - Liu, Baonian; Yang, Qinrui; Meng, Hang; Shao, Chengchen; Jiang, Jieqing; Xu, Hongmei; Sun, Kuan; Zhou, Yuxiang; Yao, Yining; Zhou, Zhihan; Li, Hui; Shen, Yiwen; et al.
Highlights: The multiplex assay is developed with 16 tissuse-specific and 2 housekeeping markers. Tissuse-specific markers in this assay presents good specificity and sensitivity to each type of body fluids. The inclusion of circRNAs in this assay helps in the identification of aged biological stains. Abstract: Currently, mRNA profiling is widely investigated for forensic body fluid identification, while it is still required to advance the approach for those casework samples of limited quantity or low quality. The inclusion of circular RNAs (circRNAs) can facilitate the detection of mRNA markers in forensic body fluid identification. In this study, a multiplex assay for forensic body fluid identification (F18plex assay) was developed by incorporating 14 tissue-specific mRNA markers with circRNAs expression, 2 mRNA markers with high abundance and 2 housekeeping markers for the discrimination of the most common forensic body fluids, including blood, menstrual blood, saliva, vaginal secretion, semen and urine. The markers employed in the F18plex assay show similar specificity to previous reports. Additionally, even if all linear transcripts were completely erased, the expected markers in target biofluids could still be identified, which should help the discrimination of those aged biological stains. Results from sensitivity testing and the detection of mixtures demonstrate good sensitivity of the multiplex assay. Generally, full biomarker profiles could be obtained with ≥1 μl of blood, saliva, or semen, and ≥1 ng of total RNAs from menstrual blood, vaginal secretion, or urine samples, respectively, using this multiplex assay under the established conditions. Collectively, the newly established multiplex assay can assist in determining the biological origin of forensic stains.